Improving the Quality and Production of Reformate - Abdulwahhab, Zeinab T.; Jawad, Qais J.; Ali, Yazen M.; Aliyawaer, Hadeel H.; Thiab, Qaiser L. (Journal of Petroleum Research and Studies, 2025)
One of the primary and most crucial units in Iraqi refineries is the gasoline reforming unit. In order to simulate and upgrade the conventional unit to the other unit configuration (Continuous Catalytic Regeneration Reformer Process (CCRRP)), it was suggested in this study to develop the gasoline reforming unit (Semi-Regenerative Catalytic Reformer Process (SRCRP)) by adding a fourth reactor (fixed bed reactor) of the same size and configuration for the last reactor of the unit that is currently used in the refinery. This study aims to investigate the effect of increasing the number of reactors on product quality. Several variables were studied in the unit, including temperature (490, 500, 510, 520, 530, and 540 ºC), pressure (8 & 12 bar), Liquid Hourly Space Velocity (LHSV) 1.5 & 4.5 hr-1, catalyst type (spent and fresh), and catalyst regeneration and pre-preparation steps (carbon burning + drying + oxychlorination + calcination + reduction + sulfiding). The results showed that the maximum increasing of RON values is 10 degrees under 12 bar and 4.5 hr-1 by applying all the regeneration and pre-preparation steps with exception of oxychlorination (for spent catalyst) but with short life period of this catalyst comparing with fresh catalyst which have high activity for long interval with 8 grades increasing in RON. In addition, the RON of the reformate at (12 bar) was higher than the octane number at (8 bar). Otherwise, the RON does not differ significantly between the two LHSV values tested (1.5 and 4.5 hr-1), indicating that the LHSV had no major influence on the product's octane number for reformate improvement by adding fourth reactor. According to the catalyst regeneration and pre-preparation method, the results indicate that the highest and longest improving of octane number was obtained when a fresh catalyst was applied in the unit by performing the pre- preparation processes which include (drying + reduction + sulfiding) for it, followed by spent catalyst with all the activation steps which include (carbon burning + drying + oxychlorination + calcination+ reduction + sulfiding).